Determinants of Islamic and Conventional Banks Profitability: A Contingency Approach - Ibrahim, Yara; Yahya, Sofri (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: The purpose of this study is to investigate the determinants of Islamic and conventional banks profitability in the Middle East and North African (MENA) regions. Design/Methodology/Approach: This study utilises multiple regression analysis using a panel data model to identify profitability determinants through convenience sampling of Islamic and conventional banks across eight countries operating in the MENA region, between 2008 to 2016. Research findings: This study found that the profitability of conventional banks measured by ROAE was higher than that of the Islamic banks. Furthermore, the liquidity and financial risk were proven to have a negative significant relationship with profitability, while the diversification strategy and human capital efficiency had a significant positive relationship with Islamic banks. The moderation effect of economic development was positive in terms of liquidity and financial risk, but negative on the diversification strategy. For conventional banks, cost leadership strategy had a significant negative relationship with profitability. The external variables including inflation rate and industry concentration had a significant effect on profitability. The moderation effect of economic development was negative with regards to the cost leadership strategy, and positive with regards to the financial risk-taking strategy. Theoretical contribution/Originality: This study is supported by relatively new theories in the field of finance, using the contingency theory, and resource-based view theory. By utilising the added economic value for measuring the Islamic bank’s profitability, in addition to the investigation on the moderation effects of the country’s income level, this is deemed a relatively new method. Practitioner/Policy implication: This study will benefit bank managers in selecting their strategies and capabilities wisely to improve their bank’s profitability. Research limitation/Implications: The existence of political and economic crisis during the research scope and the sample size was greatly affected by the unavailability of data. Keywords: Banking, Conventional, Islamic, Profitability, MENA Region JEL Classification: G21